Implementation of the Deep Learning Approach in Elementary School Mathematics Learning - Sandi Budi Iriawan; Tatat Hartati; Babang Robandi (STAI Hubbulwathan Duri, 2025)
Challenges such as limited facilities, insufficient professional training, and resistance to pedagogical innovation hinder the effective implementation of advanced learning approaches in elementary education. This study aims to analyze how the deep learning approach is implemented in mathematics instruction at the elementary school level. A qualitative research design with a case study method was employed. Participants included 29 elementary school teachers—9 from Pagerwangi I Public Elementary School and 20 from Madrasah Ibtidaiyyah Al-Haq, West Java—selected through purposive sampling. Data were collected using an observation instrument designed to assess the implementation of deep learning practices. Data analysis followed the Miles and Huberman model, involving data reduction, presentation, and conclusion drawing. The findings show that the average teacher competency score in implementing the deep learning approach was 78.06%, categorized as